2014
DOI: 10.11646/zootaxa.3780.3.8
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Anastrepha (Diptera: Tephritidae) from Euphorbia tehuacana (Euphorbiaceae) in Mexico

Abstract: Anastrepha tehuacana, a new species of Tephritidae (Diptera) from Tehuacán, Puebla, Mexico reared from seeds of Euphorbia tehuacana (Brandegee) V.W. Steinm. (Euphorbiaceae), is described and illustrated. Its probable relationship to A. relicta Hernández-Ortiz is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Previous studies reported 39 known described species of Anastrepha in Mexico [ 24 , 43 ], including recent records of Anastrepha tehuacana Norrbom [ 16 ] and Anastrepha furcata Lima [ 44 ]. For the state of Quintana Roo, there are currently 12 known species of Anastrepha [ 24 , 36 , 43 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported 39 known described species of Anastrepha in Mexico [ 24 , 43 ], including recent records of Anastrepha tehuacana Norrbom [ 16 ] and Anastrepha furcata Lima [ 44 ]. For the state of Quintana Roo, there are currently 12 known species of Anastrepha [ 24 , 36 , 43 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico and various countries of Central and South America, numerous samples of wild and cultivated tropical fruits have been examined in order to determine their seasonal phenology and infestation levels, produced mainly by Anastrepha species. In numerous occasions, such insect-plant biological interactions were recorded for the first time [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. There are few systematic studies on trophic interactions between frugivorous tephritids and their host plants in natural environments in the Americas [ 18 , 19 , 20 , 21 ], unlike those carried out in agroecosystems where only a few fruit fly species are found associated with cultivated fruits [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we identify those regions with unique interactions it could be useful in finding an explanation of how some habitats filter unique set interactions and would provide valuable information to postulate useful policies to conserve not only rare species but also rare interactions [30]. The role of rare interactions should not be overlooked, as rare or endemic species might depend on such rare interactions for their persistence and to complete their life cycles, e.g., [68]. Indeed, overarching ecological network theory argues that rare interactions are part of the non-random structure of networks that maintains biodiversity, and that without it, ecological networks are not functional [69].…”
Section: Merging Species Interactions Into Metawebs (γ-Diversity)mentioning
confidence: 99%
“…The family Tephritidae is composed of approximately 4,541 valid species grouped into 493 genera (NORRBOM, 2010). Anastrepha Schiner is considered the most economically relevant fruit ly genus in tropical America, with over 250 described species and the highest recorded number of pest species (NORRBOM, 2004a;2004b;NORRBOM et al, 2014). To date, 120 species of Anastrepha have been reported in Brazil (ZUCCHI, 2008).…”
Section: Introductionmentioning
confidence: 99%